Evaluating Effectiveness of Sustainable Livelihood Development in Rural Communities along Mara River Basin, Tanzania: What Works, What Doesn’t Work, and Why? - Edwin Estomii Ngowi; Angela M. Jesse (PLoS ONE, 2026)
The “ Sustainable Livelihood Development of Rural Communities in Low Land Along the Mara River Basin ” project, implemented by Mogabiri Farm Extension Centre (MFEC) in Tarime District, Tanzania, seeks to address persistent socio-economic challenges in rural communities by promoting climate adaptation, income diversification, and gender equality. Despite its ambitious objectives, the project operates within a complex socio-economic and cultural environment that can undermine its intended outcomes. Evaluating such projects requires a critical examination of both their successes and the barriers that persist. Using a mixed-methods approach, this evaluation combined quantitative data from 265 smallholder farmers (SHFs) and qualitative insights from focus group discussions (FGDs), key informant interviews (KIIs), and document reviews. In terms of “ What Works? ”, findings indicate that 75% of SHFs adopted climate-resilient practices ( p < 0.05), and 90% of communities implemented gender-responsive action plans ( p < 0.01), with 68% of households engaging in income diversification activities such as poultry farming and beekeeping. However, the question of “ What Doesn’t Work? ” revealed notable shortcomings, including limited market access ( p = 0.03) and cultural barriers restricting full gender participation ( p = 0.04). The persistence of these challenges, despite project successes, underscores the need for a deeper investigation into structural and contextual factors that constrain the effectiveness of such initiatives. Understanding “ Why? ” these barriers remain highlights the interplay of systemic market integration challenges and cultural resistance to gender equity. While the project has made commendable progress, addressing these underlying issues is crucial for achieving long-term success. Strengthening market linkages, expanding gender-sensitive interventions, and fostering sustainability through community ownership and local partnerships are recommended to enhance scalability and impact.